Reparations for ‘guilty victims’: navigating complex identities of victim : perpetrators in reparation mechanisms - Moffett, Luke (International journal of transitional justice, 2016)
Reparations are often declared victim-centred, but in transitional societies defining who is a victim and eligible for reparations can be politically charged and controversial. The messy reality of conflict means that perpetrators and victims do not always fall into two separate categories. In certain circumstances, perpetrators can be victimized and victims can be responsible for victimizing others - this article explores these complex victims. Looking in particular at the 1993 Shankill bombing in Northern Ireland, as well as at Colombia and Peru, such victims are often seen as ‘guilty’ or ‘bad’ victims undeserving of reparations. I argue that complex victims need to be included in reparation mechanisms to ensure accountability and to prevent their exclusion becoming a source of victimization and future violence. I consider the alternative avenues of human rights courts, development aid, services and community reparations to navigate complex identities of victim-perpetrators. I conclude that complex identities can be accommodated in transitional societies’ reparation programmes through nuanced rules of eligibility and forms of reparations.